The Trinity Cathedral Choral Singers Led By Albert Tackie (African Knowledges and the History Publication since the 1970s)
Gospel choir sings Christian and Christmas songs.
Keywords: Religion; Christianity; Music; Choirs (Music); Gospel music; Singing; Live Music